2018
DOI: 10.1080/08927014.2018.1437146
|View full text |Cite|
|
Sign up to set email alerts
|

Sodium trimetaphosphate and hexametaphosphate impregnated with silver nanoparticles: characteristics and antimicrobial efficacy

Abstract: This study aimed to synthesize and characterize materials containing silver nanoparticles (AgNP) with polyphosphates (sodium trimetaphosphate (TMP) or sodium hexametaphosphate (HMP), and evaluate their effect against Candida albicans and Streptococcus mutans. The minimum inhibitory concentration (MIC) was determined, which was followed by the quantification of the biofilm by counting colony-forming units (CFUs), the amount of metabolic activity, and the total biomass. The MICs revealed greater effectiveness of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…A sodium-hexametaphosphate-induced improvement in AgNP toxicity was also confirmed in further studies conducted by Mendes-Gouvêa et al [124]. The authors documented that the composites of AgNPs and sodium hexametaphosphate significantly reduced the formation of biofilms of C. albicans and Streptococcus mutans.…”
supporting
confidence: 59%
See 1 more Smart Citation
“…A sodium-hexametaphosphate-induced improvement in AgNP toxicity was also confirmed in further studies conducted by Mendes-Gouvêa et al [124]. The authors documented that the composites of AgNPs and sodium hexametaphosphate significantly reduced the formation of biofilms of C. albicans and Streptococcus mutans.…”
supporting
confidence: 59%
“…Enhancer of bactericidal properties of other biologically active substances [121][122][123][124] All the antioxidants applied during the synthesis of AgNPs possess well-established biocidal properties (Table 4). For this reason, it was expected that AgNPs prepared with their use should be more biocidal for the tested pathogens than TCSBAgNPs and TCAgNPs, which were coated with citrate anions.…”
mentioning
confidence: 99%
“…AgNPs, has demonstrated its antifungal effects for a long time. Various mechanisms contributed its fungicidal effect, including ROS promotion, blocking the synthesis of ATP, changing surface morphology, cellular ultrastructure, membrane microenvironment, membrane uidity, ergosterol content, and fatty acid composition [45]. Many of these factors are also crucial for drug resistance and pathogenicity of C. albicans.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in vitro showed that the mouthwash solution containing TiO 2 NPs showed superior antibacterial activity against oral pathogenic microorganisms [151]. Nanoparticles of Zn [152,153], Ag [2,154,155,156,157,158,159,160] synergistic with CHX [161,162] or doxycycline [163] showed significant antibacterial effect in an in vitro subgingival biofilm mode. Hexagonal form of boron nitride (hBN)—referred as “white graphite”—showed high antibiofilm activity on preformed biofilm and exhibited no cytotoxic effect on cells at the concentration range of 0.025–0.1 mg/mL [164].…”
Section: Antimicrobial Applications In Dentistrymentioning
confidence: 99%